Tunable superconducting resonators via on-chip control of local magnetic field - Wang, Chen-Guang; Yue, Wen-Cheng; Tu, Xuecou; Chi, Tianyuan; Guo, Tingting; Lyu, Yang-Yang; Dong, Sining; Cao, Chunhai; Zhang, Labao; Jia, Xiaoqing; Sun, Guozhu; Kang, Lin; et al. (Chinese physics B, 2024)
Superconducting microwave resonators play a pivotal role in superconducting quantum circuits. The ability to fine-tune their resonant frequencies provides enhanced control and flexibility. Here, we introduce a frequency-tunable superconducting coplanar waveguide resonator. By applying electrical currents through specifically designed ground wires, we achieve the generation and control of a localized magnetic field on the central line of the resonator, enabling continuous tuning of its resonant frequency. We demonstrate a frequency tuning range of 54.85 MHz in a 6.21-GHz resonator. This integrated and tunable resonator holds great potential as a dynamically tunable filter and as a key component of communication buses and memory elements in superconducting quantum computing.